Fulfillment of Children's Rights After Divorce : A Comparative Study in Qatar, Egypt, Indonesia, Malaysia, and Jordan - Muslih Muslih; Akbarizan Akbarizan; Akmal Abdul Munir; Akel Fernando; Andi Marwan (International Journal of Law and Society, 2025)
Divorce is a global phenomenon with significant implications for children's rights. This study aims to conduct a comparative analysis of the fulfillment of children's rights after divorce in five countries with different legal systems: Qatar, Egypt, Indonesia, Malaysia, and Jordan. The research employs a normative juridical method with a comparative legal research approach through literature review and legal document analysis. The findings reveal that each country has a unique mechanism for ensuring children's rights after divorce. Diverse legal systems—ranging from common law, civil law, to Islamic law—lead to variations in approaches to ensuring custody, care, and protection for children. The study identifies four critical dimensions in fulfilling children's rights: the right to survival and development, the right to protection, the right to education, and the right to participation. The comparative analysis highlights that cultural factors, legal systems, and political commitment play a fundamental role in determining the effectiveness of child rights protection after divorce. Key recommendations of this study include the need for regulatory harmonization, strengthening enforcement mechanisms, and developing sustainable monitoring systems. This research provides theoretical and practical contributions to understanding the complexity of fulfilling children's rights across global legal systems.